2018
DOI: 10.1186/s12939-018-0872-3
|View full text |Cite
|
Sign up to set email alerts
|

Primary care clinicians’ perspectives about quality measurements in safety-net clinics and non-safety-net clinics

Abstract: BackgroundQuality metrics, pay for performance (P4P), and value-based payments are prominent aspects of the current and future American healthcare system. However, linking clinic payment to clinic quality measures may financially disadvantage safety-net clinics and their patient population because safety-net clinics often have worse quality metric scores than non-safety net clinics. The Minnesota Safety Net Coalition’s Quality Measurement Enhancement Project sought to collect data from primary care providers’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 39 publications
(40 reference statements)
0
17
0
Order By: Relevance
“…Table 1 provides details related to the time period of program implementation since the inception of P4P in the early 2000s (early, evolving, and routinization), as well as the program design as described by the authors of each article. Nine articles were focused on studies based in the United Kingdom, 34,35,39,40,42,43,[45][46][47] 7 articles in the United States, 33,37,38,48,49,51,52 1 article each in Tanzania, 36 Malawi, 44 France, 50 and the Netherlands. 41 Twelve articles focused on physicians, nurses, and health care professionals, 5 articles focused on physicians, one of which also included practice executives, 2 articles focused on practice executives/leaders, and 1 article focused on nonphysician health care professionals.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 provides details related to the time period of program implementation since the inception of P4P in the early 2000s (early, evolving, and routinization), as well as the program design as described by the authors of each article. Nine articles were focused on studies based in the United Kingdom, 34,35,39,40,42,43,[45][46][47] 7 articles in the United States, 33,37,38,48,49,51,52 1 article each in Tanzania, 36 Malawi, 44 France, 50 and the Netherlands. 41 Twelve articles focused on physicians, nurses, and health care professionals, 5 articles focused on physicians, one of which also included practice executives, 2 articles focused on practice executives/leaders, and 1 article focused on nonphysician health care professionals.…”
Section: Resultsmentioning
confidence: 99%
“…." 37 Another study participant reflected that quality target feedback is important to show the clinical care performance. A GP remarked, "I thought I was doing well, but now I get more insight into what happens."…”
Section: Quality Targets Improve Patient Care Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 Studies conducted in the United States have shown that continuity of care improves equity, and it favors the quality of health, enabling the interaction of professionals with users, in addition to improvement in care. 11,12 Difficulties encountered by professionals to work at SUS are an impacting factor in the daily life of health services, since they compromise the implementation of SUS principles and guidelines, making it impossible to provide comprehensive care to the population. 6,13 Therefore, the proposal of this study is justified by the relevance of understanding the daily life of SUS, in its third decade, from the perspective of PHC health professionals in three cities of Minas Gerais and questioned: how is the daily practice in the SUS, in three cities of the state of Minas Gerais, Brazil, from the perspective of PHC health professionals?…”
Section: Introductionmentioning
confidence: 99%